Design And Development Of CMMS Mobile Application for Manufacturing Factory - Said Ramadhan, Nurshazreena; Kasim, Shahreen (Applied Information Technology And Computer Science, 2022)
Mobile CMMS for manufacturing factory is a mobile application to keep maintenance data for centralized access, automates tasks for increased efficiency, and aids in the management of maintenance procedures. With the development of the application, work order management and maintenance management will be more systematic and efficient. The development of this system uses Agile methodology and Scrum framework which includes 7 phases which is plan, iterate, analyze, design, develop, test and release phase. The development tools that will be used are Flutter, Android Studio and the database used is Firebase. The developed contains a login module, work order module, asset module and alert notification module. With the application, the employee is not tied to their desk, they can easily to update or make notes of the work order and maintenance while they’re on site to keep the data more accurate.